Penile amputation as to secondary to the psychopathology of shizophrenia - Maszaidi Z,; Hatta Sidi,; Muhammad Hizri H, (Faculty of Medicine, Universiti Kebangsaan Malaysia, 2016)
Schizophtrenia is a chronic mental disorder that is characterized by perceptual, thinking, cognitive, and behavioural disturbances. One of the important symptoms of schizophrenia is auditory hallucinations. In this case report, we discussed a 31-year-old Rohigya refugee man who had his penis totally amputated. The auditory hallucinations instructed him to do so. He was rushed to Universiti Kebangsaan Malaysia Medical Centre (UKMMC) for the immediate surgical treatment. After his condition was stabilized, he was admitted to the psychiatric ward for further observation and medical treatment. Some issues related to psychosocial, economic and politic were discussed which made this case unique. Patient was treated with medication sulpride and was referred to the Urology Surgeon for further management.